Epidemiology, Risk Factors, and Outcomes of Out-of-Hospital Cardiac Arrest Caused by Stroke: A Population-Based Study. Issue 14 (April 2016) - Fukuda, Tatsuma; Ohashi-Fukuda, Naoko; Kondo, Yutaka; Sera, Toshiki; Doi, Kent; Yahagi, Naoki
Abstract : Abstract: Limited information is available regarding stroke-related out-of-hospital cardiac arrest (OHCA). We aimed to assess the clinical characteristics of stroke-related OHCA and to identify the factors associated with patient outcomes. We conducted a nationwide population-based study of adult OHCA patients in Japan from January 1, 2006 to December 31, 2009. We examined the epidemiology, risk factors, and outcomes of stroke-related OHCA compared with cardiogenic OHCA. The primary outcome was neurologically favorable survival. Of the 243, 140 eligible patients, 18, 682 (7.7%) were diagnosed with stroke-related OHCA. Compared to OHCA with a presumed cardiac etiology, stroke-related OHCA patients had a greater chance of prehospital return of spontaneous circulation (ROSC) (9.9% vs 5.9%, P  < 0.0001) but a reduced chance of 1-month survival (3.6% vs 4.9%, P  < 0.0001) or favorable neurological outcomes (1.2% vs 2.6%, P  < 0.0001). After adjusting for a variety of confounding factors, the prehospital ROSC rates were higher (adjusted OR 2.47, 95% confidence interval [CI] 2.34–2.62), but the neurologically favorable survival rates were lower (adjusted OR 0.66, 95%CI 0.57–0.76), among the stroke-related OHCA patients. In stroke-related OHCA cases, having a younger age, witness, and shockable 1st documented rhythm were associated with improved outcomes. Men had more favorable neurological outcomes. Seasonal or circadian factors had no critical impact on favorable neurological outcomes. Prehospital advanced life support techniques (i.e., epinephrine administration or advanced airway management) were not associated with favorable neurological outcomes. Although stroke-related OHCA had lower 1-month survival rates and poorer neurological outcomes than cardiogenic OHCA, the rates were not considered to be medically futile. Characteristically, sex differences might impact neurologically favorable survival. Abstract : Supplemental Digital Content is available in the text